A New Navigation Function Based Decentralized Control of Multi-Vehicle Systems in Unknown Environments - Wang, Yuanzhe (2017)
This paper deals with navigation for a group of vehicles while avoiding collisions and ensuring global network connectivity in unknown environments using a new decentralized navigation function. It is pointed out that the traditional navigation function is not effective in the situation where vehicles work in a large environment. It is shown that in this situation velocity of the vehicle would be extremely small, which is not realistic in practical applications. This paper proposes a new decentralized navigation function with a novel goal function based on which a decentralized control law that is along the negative gradient of the decentralized navigation function is derived. Finally the proposed decentralized control law is applied in a multi-vehicle navigation scenario. Based on the properties of the proposed navigation function and dual Lyapunov theorem, a sufficient condition is derived for vehicles to converge to regions surrounding their corresponding goal positions in a collision-free and connectivity-keeping manner. Simulation results demonstrate the efficacy of the proposed method.